Glass product and display device
By adjusting the composition and process of glass products, glass products with excellent impact resistance are prepared, which solves the problem of easy damage to glass products in portable electronic devices and achieves high strength and flexibility in foldable display devices.
Patent Information
- Application Number
- CN202410809765.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-29
- Filing Date
- 2024-06-21
- Publication Date
- 2024-12-31
AI Technical Summary
Existing glass products are susceptible to external impact damage in portable electronic devices, and are difficult to take into account both thin thickness and impact resistance, and are more prominent in foldable display devices.
By adjusting the composition ratio and manufacturing process of the glass product, glass products with excellent impact resistance are prepared, specifically including thicknesses in the range of 20 μm to 100 μm, multiple brittleness indexes are defined to ensure their performance under external impact, combined with SiO2 , Al2O3 and metal oxides combine to form glass products with flexible and high strength using chemical and thermal reinforcement processes.
The excellent impact resistance and flexibility of glass products in the foldable display device are realized, and cracks can be effectively prevented under external impact, while meeting the transparency and physical properties requirements of the display device.
Smart Images

Figure CN119229741A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a glass article, a glass article for a cover window of a foldable display device, and a display device including the glass article. Background Art
[0002] Glass products are widely used in electronic devices including display devices or building materials. For example, glass products are applied to substrates of flat panel display devices such as liquid crystal display ("LCD") devices, organic light emitting display ("OLED") devices, or electrophoretic display devices, or cover windows for protecting the substrates.
[0003] As portable electronic devices such as smartphones and tablet personal computers (PCs) become popular, glass products applied to them are often exposed to external impacts. Therefore, it is desirable to develop glass products that are thin for portability and can withstand external impacts.
[0004] In recent years, foldable display devices are being studied for the convenience of users. Preferably, the glass product applied to the foldable display device has a thin thickness to reduce the bending stress caused when being folded, and has strength to withstand external impact. Therefore, attempts are being made to improve the strength of thin glass products by changing the composition ratio of the composition of the glass product and the manufacturing process conditions. Summary of the invention
[0005] Features of the present disclosure provide a glass article having an index defined as a predetermined physical property satisfying a predetermined value to have excellent impact resistance characteristics, and a display device including the glass article.
[0006] However, the features of the present disclosure are not limited to the features set forth herein. The above and other features of the present disclosure will become more apparent to those skilled in the art to which the present disclosure pertains by referring to the detailed description of the present disclosure given below.
[0007] The glass article in the embodiment may have a fracture energy index, an elastic energy index and a free volume index higher than or equal to a predetermined value, and thus has excellent impact resistance. Due to the foldable property of the glass article, a display device including the glass article may have excellent flexibility and strength.
[0008] However, the effects in the embodiments of the present disclosure are not limited to those exemplified above, and various other effects are incorporated herein.
[0009] In an embodiment of the present disclosure, the glass article has a thickness in a range of about 20 micrometers (μm) to about 100 μm, and a first fragility index of the glass article defined by the following equation 1 (hereinafter also referred to as equation 1 (Eq. 1)) is about 1.5×10 -4μm 0.5 or larger:
[0010] The first brittleness index = 1 / B = K IC / H v (μm 0.5 )[Equation 1]
[0011] Among them, "B" is brittleness, "K" is IC ” is the fracture toughness, and “H v ” is the hardness, and the tensile index defined by the following equation (2′) (hereinafter also referred to as equation (2′) (Eq. (2′))) is about 0.95 or greater:
[0012]
[0013] Where "D" is the strength coefficient (D = B VFT / T 0 ), "T 0 ” is the Vogel temperature, “B VFT "It is in T 0 The viscosity under the condition of "T g ” is the glass transition temperature.
[0014] In an embodiment, the second brittleness index defined by the following equation 2 (hereinafter also referred to as equation 2 (Eq. 2)) may be approximately 2.3×10 -10 MPa·m or greater:
[0015] The second brittleness index = 1 / B×K IC (MPa·m)[Equation 2]
[0016] Where "B" is the brittleness, and "K IC ” is the fracture toughness.
[0017] In an embodiment, the third brittleness index defined by the following equation 3 (hereinafter also referred to as equation 3 (Eq. 3)) may be approximately 2.0×10 -7 μm 0.5 / K:
[0018] The third brittleness index = 1 / B × 1 / T g (μm 0.5 / K)[Equation 3]
[0019] Where "B" is the brittleness, and "T g ” is the glass transition temperature.
[0020] In an embodiment, the fourth brittleness index defined by the following equation 4 (hereinafter also referred to as equation 4 (Eq. 4)) may be approximately 1.6×10-2 MPa·μm 0.5 / K or greater:
[0021] The fourth brittleness index = 1 / B × 1 / T g ×E(MPa·μm 0.5 / K)[Equation 4]
[0022] Wherein, “B” is the brittleness, “T g ” is the glass transition temperature, and “E” is the Young’s modulus.
[0023] In an embodiment, in a pen drop test performed with a pen having a ball diameter of about 0.7 millimeters (mm) and a weight of about 1.12 g, a crack occurrence height may be about 6 cm or more.
[0024] In an embodiment, the glass article may be flexible.
[0025] In an embodiment, the glass transition temperature may be equal to or lower than 600°C.
[0026] In an embodiment, the glass article may include SiO 2 、Al 2 O 3 and except Al 2 O 3 Other metal oxides or SiO 2 、Al 2 O 3 and except Al 2 O 3 The metal oxide composition other than Al is defined as the flux of the ratio of the content of the monovalent metal oxide to the content of the divalent metal oxide in the metal oxide can be in the range of 5 to 10, and Al 2 O 3 The ratio of the content of to the total content of the metal oxides may be in the range of 0.2 to 0.6.
[0027] In an embodiment of the present disclosure, a glass article for a cover window of a foldable display device has a thickness in a range of about 20 μm to about 100 μm, and a first fragility index of the glass article defined by the following equation 1 is about 1.5×10 -4 μm 0.5 or larger:
[0028] The first brittleness index = 1 / B = K IC / H v (μm 0.5 )[Equation 1]
[0029] Among them, "B" is brittleness, "K" is IC” is the fracture toughness, and “H v ” is hardness, in a pen drop test performed with a pen having a ball diameter of about 0.7 mm and a weight of about 1.12 g, a crack occurrence height is about 6 cm or more, and the glass article has flexibility.
[0030] In an embodiment of the present disclosure, a display device includes: a display panel including a plurality of pixels; a cover window disposed above the display panel; and an optically transparent bonding layer disposed between the display panel and the cover window, wherein the cover window includes a glass article having a thickness in a range of about 20 μm to about 100 μm and having a first brittleness index defined by the following equation 1, wherein the first brittleness index is about 1.5×10 -4 μm 0.5 or larger:
[0031] First brittleness index = 1 / B = K IC / H v (μm 0.5 )[Equation 1]
[0032] Among them, "B" is brittleness, "K" is IC ” is the fracture toughness, and “H v " is a hardness and has a tensile index defined by the following equation (2'), the tensile index being 0.95 or greater:
[0033]
[0034] Where "D" is the strength coefficient (D = B VFT / T 0 ), "T 0 ” is the Vogel temperature, “B VFT "It is in T 0 The viscosity under the condition of "T g ” is the glass transition temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The above and other embodiments and features of the present disclosure will become more apparent by describing in detail embodiments of the present disclosure with reference to the accompanying drawings, in which:
[0036] Figure 1 is a perspective view of an embodiment of a glass article;
[0037] Figure 2 is a perspective view showing an embodiment in which a glass article in an unfolded state is applied to a display device;
[0038] Figure 3 The folded state is shown Figure 2 A perspective view of a display device;
[0039] Figure 4 is a cross-sectional view showing an embodiment in which a glass article is applied to a cover window of a display device;
[0040] Figure 5 is a cross-sectional view of an embodiment of a glass article having a flat plate shape;
[0041] Figure 6 is a graph showing an example of stress distribution of a glass article;
[0042] Figure 7 is a flow chart illustrating an embodiment of the operation of a process for manufacturing a glass article;
[0043] Figure 8 It is schematically shown Figure 7 A diagram of operations from a cutting operation to a surface polishing operation after strengthening; and
[0044] Fig. 9 is a diagram showing an embodiment of a pen drop test method for a glass product. DETAILED DESCRIPTION
[0045] Embodiments of the present disclosure will now be described more fully below with reference to the accompanying drawings, in which preferred embodiments of the present invention are shown. However, the present invention may be implemented in different forms and should not be construed as being limited to the embodiments set forth herein. On the contrary, these embodiments are provided so that the present disclosure will be thorough and complete, and will fully convey the scope of the present invention to those skilled in the art.
[0046] It will also be understood that when a layer or substrate is referred to as being “on” another layer or substrate, it can be directly on the other layer or substrate, or intervening layers may also be present. Throughout the specification, the same reference numerals refer to the same components.
[0047] It will be understood that although the terms "first", "second", etc. may be used herein to describe various elements, these elements should not be limited by these terms. These terms are only used to distinguish one element from another element. For example, without departing from the teachings of the present invention, the first element discussed below may be referred to as the second element. Similarly, the second element may also be referred to as the first element.
[0048] As used herein, "about" or "approximately" includes the stated value and means within an acceptable range of deviation for the particular value as determined by one of ordinary skill in the art, taking into account the measurement in question and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system). The term "about" can mean within one or more standard deviations, or, for example, within ±30%, ±20%, ±10%, or ±5% of the stated value.
[0049] Hereinafter, embodiments will be described with reference to the accompanying drawings.
[0050] Figure 1 is a perspective view of an embodiment of a glass article.
[0051] Glass is used as a cover window for protecting a display, a substrate for a display panel, a substrate for a touch panel, or an optical member such as a light guide plate in electronic devices including a display, such as a tablet personal computer ("PC"), a notebook PC, a smart phone, an electronic book, a television, and a PC monitor, and a refrigerator and a cleaning machine including a display. Glass may also be used as a cover glass for an instrument panel of a vehicle, a cover glass for a solar cell, an interior material for a building material, or a window for a building and a house, etc.
[0052] It is desirable that the glass has relatively high strength. In an embodiment, when the glass is used as a window, it is desirable to have a relatively small thickness to satisfy the desired conditions of relatively high transmittance and light weight, and also have a strength such that the glass is not easily damaged by, for example, external impact. Strengthened glass can be produced by, for example, chemical strengthening or thermal strengthening. In an embodiment, Figure 1 Strengthened glasses having various shapes are shown in FIG.
[0053] refer to Figure 1 In an embodiment, the glass article 100 may have a flat sheet shape or a flat plate shape. In another embodiment, the glass articles 101, 102, and 103 may have a three-dimensional shape including a bent portion. In an embodiment, for example, the edge of the flat portion may be bent (e.g., glass article 101), or the flat portion may be completely curved (e.g., glass article 102) or folded (e.g., glass article 103). In an alternative embodiment, the glass article 100 may have a flat sheet shape or a flat plate shape, and may be flexibly folded, stretched, or rolled.
[0054] The plane shape of the glass articles 100 to 103 may be a quadrilateral shape (e.g., a rectangular shape), but is not limited thereto, and may have various shapes, such as a rectangular shape with rounded corners, a square shape, a circular shape, and an elliptical shape. In the following embodiments, a flat plate having a quadrilateral shape (e.g., a rectangular shape) is described in the embodiments of the glass articles 100 to 103, but the present disclosure is not limited thereto. In an embodiment, the glass articles 100, 101, 102, and 103 may each include a first surface US, a second surface RS, and a side surface SS.
[0055] Figure 2 is a perspective view showing an embodiment in which a glass article in an unfolded state is applied to a display device. Figure 3 The folded state is shown Figure 2 A perspective view of a display device.
[0056] refer to Figure 2 and Figure 3 , the display device 500 in the embodiment may be a foldable display device. As will be described later, in the display device 500, Figure 1 The glass article 100 may be applied to a cover window, and the glass article 100 may be flexible (eg, foldable).
[0057] exist Figure 2 and Figure 3 , the first direction DR1 may be a direction parallel to one side of the display device 500 in a plan view, and may be, for example, a horizontal direction of the display device 500. The second direction DR2 may be a direction parallel to the other side in contact with the one side of the display device 500 in a plan view, and may be, for example, a vertical direction of the display device 500. The third direction DR3 may be a thickness direction of the display device 500.
[0058] In an embodiment, the display device 500 may have a quadrilateral shape (e.g., a rectangular shape) in a plan view. The display device 500 may have a rectangular shape with right angles or rounded corners in a plan view. The display device 500 may include two short sides arranged in a first direction DR1 and two long sides arranged in a second direction DR2 in a plan view.
[0059] The display device 500 includes a display area DA and a non-display area NDA. In a plan view, the shape of the display area DA may correspond to the shape of the display device 500. In an embodiment, for example, when the display device 500 has a quadrilateral shape (e.g., a rectangular shape) in a plan view, the display area DA may also have a quadrilateral shape (e.g., a rectangular shape).
[0060] The display area DA may be an area including a plurality of pixels to display an image. The plurality of pixels may be arranged in a matrix. The plurality of pixels may have a quadrilateral shape (e.g., a rectangular shape, a diamond shape, or a square shape) in a plan view, but is not limited thereto. In an embodiment, for example, the plurality of pixels may have a quadrilateral shape other than a rectangular shape, a diamond shape, or a square shape, a polygonal shape other than a quadrilateral shape, a circular shape, or an elliptical shape.
[0061] The non-display area NDA may be an area that does not include pixels and does not display an image. The non-display area NDA may be disposed around the display area DA. The non-display area NDA may be disposed to surround the display area DA, but is not limited thereto. The display area DA may be partially surrounded by the non-display area NDA.
[0062] In an embodiment, the display device 500 can maintain two states: a folded state and an unfolded state. Figure 3 As shown in , the display device 500 can be folded in an inner folding manner with the display area DA disposed inside thereof. When the display device 500 is folded in an inner folding manner, the top surfaces of the display device 500 can be disposed to face each other. In another embodiment, the display device 500 can be folded in an outer folding manner with the display area DA disposed outside. When the display device 500 is folded in an outer folding manner, the bottom surfaces of the display device 500 can be disposed to face each other.
[0063] In an embodiment, the display device 500 may be a foldable device. As used herein, the term "foldable device" refers to a device that can be folded, and is used not only to mean a folding device, but also to mean a device that can have both a folded state and an unfolded state. In addition, folding may generally include folding at an angle of about 180 degrees. However, the present disclosure is not limited thereto, and folding may include a case where the folding angle exceeds about 180 degrees or is less than about 180 degrees (e.g., a case where the folding angle is equal to or greater than about 90 degrees and less than about 180 degrees or a case where the folding angle is equal to or greater than about 120 degrees and less than about 180 degrees). In addition, when folding is performed from an unfolded state, it may also be referred to as a folded state even when a complete folding is not performed. In an embodiment, even when it is folded at an angle of about 90 degrees or less, as long as the maximum folding angle becomes about 90 degrees or more, it may be expressed as being in a folded state to distinguish it from an unfolded state. During folding, the radius of curvature may be about 5 millimeters (mm) or less, preferably in a range of about 1 mm to about 2 mm or about 1.5 mm, but is not limited thereto.
[0064] In an embodiment, the display device 500 may include a folding area FDA, a first non-folding area NFA1, and a second non-folding area NFA2. The folding area FDA may be an area where the display device 500 is folded, and the first non-folding area NFA1 and the second non-folding area NFA2 may be areas where the display device 500 is not folded.
[0065] The first non-folding area NFA1 may be disposed on one side (eg, upper side) of the folding area FDA. The second non-folding area NFA2 may be disposed on the other side (eg, lower side) of the folding area FDA. The folding area FDA may be an area bent with a predetermined curvature.
[0066] In an embodiment, the folding area FDA of the display device 500 may be determined at a predetermined position. One or two or more folding areas FDA may be determined at a predetermined position (predetermined positions) in the display device 500. In another embodiment, the position of the folding area FDA may not be specified in the display device 500 and may be freely set in various areas.
[0067] In an embodiment, the display device 500 may be foldable in the second direction DR2. Therefore, the length of the display device 500 in the second direction DR2 may be reduced to approximately half, so that the user may conveniently carry the display device 500.
[0068] In an embodiment, the direction in which the display device 500 is folded is not limited to the second direction DR2. In an embodiment, the display device 500 may be folded in the first direction DR1. In this case, for example, the length of the display device 500 in the first direction DR1 may be reduced to approximately half.
[0069] In the drawings, it is shown that each of the display area DA and the non-display area NDA overlaps with the folding area FDA, the first non-folding area NFA1, and the second non-folding area NFA2, but the present disclosure is not limited thereto. In an embodiment, for example, each of the display area DA and the non-display area NDA may overlap with at least one of the folding area FDA, the first non-folding area NFA1, and the second non-folding area NFA2.
[0070] Figure 4 is a cross-sectional view showing an embodiment in which a glass article is applied to a cover window of a display device.
[0071] refer to Figure 4 The display device 500 may include a display panel 200, a glass article 100 disposed on the display panel 200 and serving as a cover window, and an optically transparent bonding layer 300 disposed between the display panel 200 and the glass article 100 to bond the display panel 200 and the glass article 100 to each other.
[0072] In an embodiment, the display panel 200 may include not only self-luminous display panels such as an organic light emitting display ("OLED") panel, an inorganic electroluminescent ("EL") display panel, a quantum dot light emitting display ("QLED") panel, a micro light emitting diode ("LED") display panel, a nano LED display panel, a plasma display panel ("PDP"), a field emission display ("FED") panel, and a cathode ray tube ("CRT") display panel, but may also include light receiving display panels such as a liquid crystal display ("LCD") panel and an electrophoretic display ("EPD") panel.
[0073] The display panel 200 includes a plurality of pixels PX, and an image can be displayed by light emitted from each pixel PX. The display device 500 may further include a touch member (not shown). In an embodiment, the touch member may be embedded in the display panel 200. In an embodiment, for example, since the touch member is directly formed on the display member of the display panel 200, the display panel 200 itself may perform a touch function. In another embodiment, the touch member may be manufactured separately from the display panel 200, and then attached to the top surface of the display panel 200 by an optically transparent bonding layer 300.
[0074] The glass article 100 is disposed above the display panel 200 to protect the display panel 200. Since the glass article 100 is larger in size than the display panel 200, the side surface SS of the glass article 100 may protrude outward from the side surface of the display panel 200, but is not limited thereto. The display device 500 may further include a printed layer (not shown) disposed on at least one surface of the glass article 100 at an edge portion of the glass article 100. The printed layer may prevent a frame region of the display device 500 from being visible from the outside, and may perform a decorative function in some cases.
[0075] The optically transparent bonding layer 300 is disposed between the display panel 200 and the glass article 100. The optically transparent bonding layer 300 is used to fix the glass article 100 to the display panel 200. The optically transparent bonding layer 300 may include an optically clear adhesive ("OCA") or an optically clear resin ("OCR"), etc.
[0076] Hereinafter, the strengthened glass article 100 will be described in more detail.
[0077] Figure 5 is a cross-sectional view of an example of a glass article having a flat plate shape.
[0078] refer to Figure 5, the glass article 100 may include a first surface US, a second surface RS, and a side surface SS. In the glass article 100 having a flat plate shape, the first surface US and the second surface RS are main surfaces having relatively large areas, and the side surface SS is an outer surface connecting the first surface US and the second surface RS.
[0079] The first surface US and the second surface RS are opposite to each other in the thickness direction. When the glass article 100 is used to transmit light in the same manner as a cover window of a display, light can be mainly incident on one of the first surface US and the second surface RS and pass through the other of the first surface US and the second surface RS.
[0080] The thickness t of the glass article 100 is defined as the distance between the first surface US and the second surface RS. The thickness t of the glass article 100 may be, but is not limited to, about 100 micrometers (μm) or less, preferably in the range of about 20 μm to about 100 μm. In an embodiment, the thickness t of the glass article 100 may be about 80 μm or less. In another embodiment, the thickness t of the glass article 100 may be about 75 μm or less. In another embodiment, the thickness t of the glass article 100 may not be about 70 μm or less. In another embodiment, the thickness t of the glass article 100 may be about 65 μm or less. In another embodiment, the thickness t of the glass article 100 may be about 60 μm or less. In another embodiment, the thickness t of the glass article 100 may be about 50 μm or less. In another embodiment, the thickness t of the glass article 100 may be about 30 μm or less. In some predetermined examples, the thickness t of the glass article 100 may be in the range of about 20 μm to about 50 μm, or may be about 30 μm. The glass article 100 may have a uniform thickness t, but is not limited thereto, and may have a different thickness t for each region.
[0081] The glass article 100 may be strengthened to have a predetermined stress distribution therein. Compared to the glass article 100 before strengthening, the strengthened glass article 100 more effectively prevents the generation of cracks, the propagation of cracks or breakage caused by external impact. The glass article 100 strengthened by the strengthening process may have different stresses for each region. In an embodiment, for example, the compression regions CSR1 and CSR2 to which the compressive stress is applied may be disposed near the surface of the glass article 100, that is, close to the first surface US and the second surface RS, and the tensile region CTR to which the tensile stress is applied may be disposed inside the glass article 100. The boundary between the compression regions CSR1 and CSR2 and the tensile region CTR (that is, the first compression depth DOC1 and the second compression depth DOC2) may have a zero stress value. The compressive stress in one compression region CSR1 or CSR2 may vary in the stress value of the compressive stress depending on the position (that is, the depth from the surface). In addition, the tensile region CTR may have different stress values depending on the depth from the surface US or RS.
[0082] The position of the compression region CSR1 or CSR2 in the glass article 100, the stress distribution in the compression region CSR1 or CSR2, the compression energy of the compression region CSR1 or CSR2, or the tension energy of the tension region CTR, etc. can have a significant impact on the mechanical properties (such as surface strength) of the glass article 100.
[0083] Figure 6 is a graph showing an example of stress distribution of a glass product. Figure 6 In the graph of , the horizontal axis represents the thickness direction of the glass product. Figure 6 In the present invention, compressive stress has a positive value, while tensile stress has a negative value. In this article, the magnitude of compressive stress / tensile stress refers to the magnitude of the absolute value, regardless of its sign.
[0084] refer to Figure 6 , glass products 100 (see Figure 5 ) includes a first compression region CSR1 extending (or expanding) from the first surface US to a first compression depth DOC1 and a second compression region CSR2 extending (or expanding) from the second surface RS to a second compression depth DOC2. The tension region CTR is disposed between the first compression depth DOC1 and the second compression depth DOC2. The overall stress distribution in the glass article 100 may be between the two regions of the surfaces US and RS with respect to the thickness t (see Figure 5 ) is symmetrical in the direction of the center. Figure 6 Not shown in FIG. 1 , but the compression region and the tension region may be disposed between the opposing side surfaces of the glass article 100 in a similar manner.
[0085] The first compression region CSR1 and the second compression region CSR2 resist external impacts to prevent the glass article 100 from cracking or breaking. The greater the maximum compressive stresses CS1 and CS2 of the first compression region CSR1 and the second compression region CSR2, the greater the strength of the glass article 100. Since external impacts are generally transmitted through the surface of the glass article 100, it is advantageous to have the maximum compressive stresses CS1 and CS2 at the surface of the glass article 100 in terms of durability. From this perspective, the compressive stresses of the first compression region CSR1 and the second compression region CSR2 tend to be maximum at the surface and generally decrease toward the inside. In an embodiment, the first compression region CSR1 and the second compression region CSR2 may include a first transition point TP1 and a second transition point TP2, respectively, at which the slope of the stress distribution changes abruptly.
[0086] The first compression depth DOC1 and the second compression depth DOC2 suppress the cracks or grooves defined in the first surface US and the second surface RS from propagating to the tensile region CTR inside the glass article 100. The larger the first compression depth DOC1 and the second compression depth DOC2, the more effectively the propagation of cracks, etc. can be prevented. Points corresponding to the first compression depth DOC1 and the second compression depth DOC2 correspond to the boundaries between the compression regions CSR1 and CSR2 and the tensile region CTR, and have a stress value of zero.
[0087] The tensile stress of the tensile region CTR may be balanced with the compressive stress of the compressive regions CSR1 and CSR2 throughout the glass article 100. That is, the total compressive stress (i.e., total compressive energy) in the glass article 100 may be the same as the total tensile stress (i.e., total tensile energy) in the glass article 100. The stress energy accumulated in one region having a constant width in the thickness t direction in the glass article 100 may be calculated as an integral value of the stress distribution. When the stress distribution in the glass article 100 having a thickness t is represented as a function f(x), the following equation A may be established.
[0088] [Equation A]
[0089]
[0090] The greater the magnitude of the tensile stress in the glass article 100, the more likely the fragments will be violently released when the glass article 100 breaks, and the more likely the glass article 100 will break from the inside. 1 The following inequality 1 may be satisfied (but is not limited to).
[0091] [Inequality 1]
[0092] CT 1≤-38.7×ln(t)+48.2
[0093] In some embodiments, the maximum tensile stress CT 1 It may be about 100 MPa or less, or 85 MPa or less. A maximum tensile stress CT of about 75 MPa or more 1 It may be desirable to improve mechanical properties such as strength. In an embodiment, the maximum tensile stress CT 1 It may be greater than or equal to about 75 MPa and less than or equal to about 85 MPa, but is not limited thereto.
[0094] Maximum tensile stress CT of glass product 100 1 It can be generally disposed at the center portion of the glass article 100 in the thickness t direction. In an embodiment, the maximum tensile stress CT of the glass article 100 1 It may be disposed at a depth in the range of about 0.4t to about 0.6t, or at a depth in the range of about 0.45t to about 0.55t, or at a depth of about 0.5t.
[0095] In order to increase the strength of the glass article 100, it is preferred that the compressive stress and the compression depths DOC1 and DOC2 have relatively large values. However, as the compressive energy increases, the tensile energy also increases, and the maximum tensile stress CT 1 It can be increased. In order to meet the desired brittleness condition and have relatively high strength at the same time, it is desirable to adjust the stress distribution so that the maximum compressive stresses CS1 and CS2 and the compression depths DOC1 and DOC2 have relatively large values while the compression energy becomes small. To this end, the glass article 100 can be manufactured by a glass composition containing a predetermined component at a predetermined content or consisting of a predetermined component at a predetermined content. According to the composition ratio of the components contained in the glass composition, the manufactured glass article 100 can have excellent strength and can have flexibility and physical properties to be applied to a foldable display device.
[0096] In an embodiment, the glass composition forming the glass article 100 may include SiO 2 、Al 2 O 3 、Na 2 O. Li 2 O, CaO or MgO and ZrO 2 .
[0097] SiO 2 It can form the skeleton of glass, and when a scratch (indentation) is formed on the glass surface, SiO 2 Can be used to increase chemical durability and reduce the occurrence of cracks. SiO 2It may be a network former oxide that forms a network of glass and contains SiO 2 Or by SiO 2 The composed manufactured glass article 100 may have a reduced coefficient of thermal expansion and improved mechanical strength.
[0098] Al 2 O 3 Used to improve the breakage resistance of glass. That is, when the glass breaks, Al 2 O 3 Can be used to produce a smaller number of fragments. 2 O 3 It can be SiO 2 The intermediate oxide that forms the bond. In addition, Al 2 O 3 It can be used as an active component to improve ion exchange performance during chemical strengthening and increase surface compressive stress after strengthening.
[0099] Na 2 O is used to form surface compressive stress through ion exchange and improve the solubility of the glass. 2 O can form a network structure with SiO 2 The oxygen forms ionic bonds to SiO 2 Non-bridging oxygen is formed in the network structure. The increase of non-bridging oxygen can improve the flexibility and impact absorption function of the network structure, and the glass article 100 can have physical properties suitable for a foldable display device.
[0100] As described above, Na 2 O is similar to Li 2 O is used to form surface compressive stress through ion exchange and improve the solubility of the glass. 2 O can form a network structure with SiO 2 The oxygen forms ionic bonds to SiO 2 Non-bridging oxygen is formed in the network structure. The increase of non-bridging oxygen can improve the flexibility and impact absorption function of the network structure, and the glass article 100 can have physical properties suitable for a foldable display device.
[0101] MgO can improve the surface strength of glass and reduce the formation temperature of glass. MgO can be a SiO 2 MgO can reduce the refractive index of glass and adjust the thermal expansion coefficient and elastic modulus of glass. CaO can improve the surface strength of glass. CaO can be a network modifier oxide for SiO2 to form a network structure. 2CaO is a modified network modifier oxide. CaO can increase the glass transition temperature of the glass and improve chemical durability.
[0102] ZrO 2 It can improve the transmittance and surface strength of glass and increase the resistance to surface crack propagation. ZrO 2 It can be SiO 2 An intermediate oxide that forms a bond. ZrO 2 Can be used with SiO 2 The bonds in the network structure are Li 2 O and Na 2 O breaks some of the bonds, thereby increasing the fracture toughness of the glass and increasing its resistance to bending.
[0103] In addition to the above components, the glass composition may also include P 2 O 5 , B 2 O 3 , K 2 O、SnO 2 , Y 2 O 3 ,La 2 O 3 , Nb 2 O 5 、 2 O 5 or Gd 2 O 3 In addition, a relatively small amount of Sb 2 O 3 、CeO 2 and / or As 2 O 3 As a clarifying agent.
[0104] The glass article 100 manufactured by the glass composition in the embodiment may have characteristics and physical properties suitable for a foldable display device. In the embodiment, for example, the glass article 100 may have flexibility to be folded and unfolded, and may have sufficient strength to be applied to the display device 500 (see Figure 2 ) of the cover window. In addition, the glass composition can provide flexibility so that the glass article 100 can be folded and unfolded. The folding and unfolding characteristics of the glass article 100 can be improved by reducing the glass transition temperature and elastic modulus of the glass. That is, because the elastic modulus of the glass is reduced, the stress applied to the lower part of the glass article 100 during folding and unfolding is reduced, thereby improving the bending characteristics of the glass article 100.
[0105] The glass composition having the above-mentioned components can be formed into a plate glass shape by various methods known in the art. When it is formed into a plate glass shape, it can be further processed and manufactured into a glass product 100 suitable for the display device 500. However, the present disclosure is not limited thereto, and the glass composition may not be formed into a plate glass shape, and may be directly formed into a glass product 100 suitable for a product without an additional forming process.
[0106] Hereinafter, a process of forming the glass composition into a plate glass shape and processing the glass into the glass article 100 will be described.
[0107] Figure 7 is a flow chart illustrating an embodiment of the operations of a process for manufacturing a glass article. Figure 8 It is schematically shown Figure 7 A diagram of the operations from the cutting operation to the surface polishing operation after strengthening.
[0108] refer to Figure 7 and Figure 8 , for producing glass products 100 (see Figure 1 ) may include a forming operation S1, a cutting operation S2, a side polishing operation S3, an enhanced front surface polishing operation S4, an enhanced operation S5, and an enhanced rear surface polishing operation S6.
[0109] The forming operation S1 may include preparing a glass composition and forming the glass composition. The glass composition may have the components described above. A detailed description thereof is omitted. The glass composition may be formed into a plate glass shape by a method such as a float process, a fusion drawing process, or a slot drawing process.
[0110] The glass formed into a flat plate shape can be cut by the cutting operation S2. The glass formed into a flat plate shape can have a size different from the size of the final glass product 100. In an embodiment, for example, glass molding can be performed to form a large-area substrate as a mother glass substrate 10a including a plurality of glass products. The mother glass substrate 10a can be cut into a plurality of units 10 (hereinafter, also referred to as cut glass 10) to produce a plurality of glass products. In an embodiment, for example, although the final glass product 100 has a size of about 6 inches, when the glass is formed to have a size several to several hundred times (for example, about 120 inches) and then cut, 20 glass products formed into a flat plate shape can be obtained at one time. In this way, compared with the case of molding a single glass product separately, process efficiency can be improved. In addition, even when molding glass corresponding to the size of one glass product, when the final glass product 100 has various planar shapes, it can be made into a desired shape by a cutting process.
[0111] The cutting of the mother glass substrate 10 a may be performed using a cutting blade 20 , a cutting wheel, a laser, or the like.
[0112] The cutting operation S2 of the glass may be performed before the strengthening operation S5 of the glass. The mother glass substrate 10a may be immediately strengthened and then cut into the size of the final glass product 100. However, in this case, the cut surface (e.g., the side surface of the glass) may be in a non-strengthened state. Therefore, it may be preferable to perform the strengthening operation S5 after the cutting operation S2 is completed.
[0113] Between the cutting operation S2 and the strengthening operation S5 of the glass, a pre-strengthening polishing operation may be performed. The polishing operation may include a side polishing operation S3 and a pre-strengthening surface polishing operation S4. In an embodiment, after the side polishing operation S3 is first performed, the pre-strengthening surface polishing operation S4 may be performed, but the order may be reversed.
[0114] The side polishing operation S3 is an operation of polishing the side surface of the cut glass 10. In the side polishing operation S3, the side surface of the cut glass 10 is polished to have a smooth surface. In addition, each side surface of the cut glass 10 can have a uniform surface through the side polishing operation S3. More specifically, the cut glass 10 may include one or more cut surfaces. In some cut glasses 10, two of the four side surfaces may be cut surfaces. In some other cut glasses 10, three of the four side surfaces may be cut surfaces. In some other cut glasses 10, all four side surfaces may be cut surfaces. When the side surface is a cut surface, it may have a surface roughness different from the surface roughness of the uncut surface. In addition, even the cut surface may have a different surface roughness. Therefore, by polishing each side surface via the side polishing operation S3, each side surface may have a uniform surface roughness, etc. In addition, when there are relatively small cracks on the side surface, they can be removed by the side polishing operation S3.
[0115] The side surface polishing operation S3 may be simultaneously performed on the plurality of cut glasses 10. That is, in a state where the plurality of cut glasses 10 are stacked, the stacked cut glasses 10 may be simultaneously polished.
[0116] The side polishing operation S3 may be performed by a mechanical polishing method or a chemical mechanical polishing method using the polishing apparatus 30. In an embodiment, two opposing side surfaces of the cut glass 10 may be polished simultaneously, and then another two opposing side surfaces may be polished simultaneously, but the present invention is not limited thereto.
[0117] The strengthening front surface polishing operation S4 may be performed to remove surface flaws by etching each cut glass 10 and to have a uniform surface. In an embodiment, the strengthening front surface polishing operation S4 may be performed by an etching process.
[0118] After the strengthening front surface polishing operation S4, the strengthening operation S5 is performed. The strengthening operation S5 may include chemical strengthening and / or thermal strengthening. In the case where the cut glass 10 has a thin thickness of about 2 mm or less, in particular, about 0.75 mm or less, the chemical strengthening method may be appropriately applied to precise stress distribution control.
[0119] After the strengthening operation S5, optionally, a post-strengthening surface polishing operation S6 may be further performed. The post-strengthening surface polishing operation S6 may remove fine cracks on the surface of the strengthened cut glass 10, and control the compressive stress of the first surface and the second surface of the strengthened cut glass 10. In an embodiment, for example, a float process, which is one of the various methods for manufacturing a glass sheet, is performed by flowing a glass composition into a tin bath. In this case, the surface of the glass sheet in contact with the tin bath may have a different composition from the surface of the glass sheet not in contact with the tin bath. As a result, after the strengthening operation S5 of the cut glass 10, a deviation in compressive stress may occur between the surface in contact with the tin bath and the surface not in contact with the tin bath. However, by polishing to remove the surface of the cut glass 10 to an appropriate thickness, the deviation in compressive stress between the contact surface and the non-contact surface may be reduced.
[0120] In an embodiment, the post-strengthening surface polishing operation S6 may be performed by chemical etching polishing. The polishing thickness may be adjusted (eg, within a range of about 100 nm to about 1000 nm), but is not limited thereto. The polishing thickness of the first surface and the second surface may be the same or may be different.
[0121] Although not shown in the drawings, after the post-strengthening surface polishing operation S6, a shape machining process may be further performed as needed. Figure 1 In the case of the glass articles 101 to 103 having a three-dimensional shape as shown in FIG. 1 , a three-dimensional machining process may be performed after completing the post-strengthening surface polishing operation S6 .
[0122] As described above, the glass article 100 manufactured by the above process can be applied to a display device 500 (see FIG. Figure 2 ) cover window. The glass article 100 may have flexibility (eg, foldable properties). In addition, the glass article 100 may have sufficient impact resistance to be applied to the cover window.
[0123] The impact resistance of the glass article 100 may be related to various mechanical and chemical properties of the glass article 100. In an embodiment, for example, the glass article 100 may have properties such as thermal expansion coefficient, transition temperature, density, Young's modulus, Poisson's ratio, Vickers hardness (also referred to as hardness), fracture toughness or brittleness, etc. The physical property may be measured by a sample of the glass article 100. Generally, when the value of the physical property exceeds a predetermined level but its reference value may not be clear, the glass article 100 may have excellent impact resistance. In an embodiment, for example, in the case of comparing the physical properties of various glass articles 100, it may be difficult to predict that the glass article 100 whose predetermined physical property has a relatively high value necessarily has better resistance to external impact (impact resistance) than other glass articles 100. This means that various physical properties of the glass article 100 need to be comprehensively evaluated to determine whether it has excellent impact resistance, making it impossible to simply evaluate the impact resistance of the glass article 100 by the measurable physical properties of the glass article 100. In particular, when the glass article 100 is applied to a cover window of the display device 500 , the correlation between the impact resistance characteristics of the glass article 100 and the values of the physical properties of the glass article 100 may not be clear.
[0124] The pen drop test is used as one of various indices for evaluating the impact resistance of the glass article 100. In the case where various glass articles 100 are prepared as predetermined samples and the pen drop test is performed, as the height at which cracks or damages begin to occur in the pen in the glass article sample becomes higher, the impact resistance of the glass article 100 may become more excellent. That is, the pen drop test result may be a clear standard for evaluating the impact resistance of the glass article 100, rather than a value of a physical property of the glass article 100.
[0125] Whether the glass article 100 is damaged may be affected by upper and lower damage in the region to which the impact is applied and structural changes of molecules constituting the glass article 100. When the glass article 100 has relatively high resistance to upper and lower damage, the glass article 100 may be subjected to external impact. When there is a free space between molecules constituting the glass article 100, the molecular structure is easily changed, and the glass article 100 may be subjected to external impact.
[0126] In an embodiment, the glass article 100 may have factors that may be quantifiable and derived as measurable physical properties, and the quantified factors may have a relatively high consistency with a pen drop test result that is a clear standard for impact resistance characteristics. Therefore, the pen drop test result and the impact resistance characteristics of the glass article 100 may be predicted by the value of the predetermined factor, and the impact resistance characteristics of the glass article 100 may be improved by improving the value of the corresponding factor. The glass article 100 may have excellent pen drop characteristics (i.e., impact resistance characteristics) because the predetermined factor to be described below has a predetermined value or more. Hereinafter, various factors that are highly consistent with the pen drop test result will be described as various factors that can be derived from the measurable physical properties of the glass article 100.
[0127] A first brittleness index, which is an index related to brittleness as a main factor for lower damage of the glass article 100 against external impact, may be defined by the following Equation 1 (hereinafter also referred to as Equation 1 (Eq. 1)).
[0128] First brittleness index = 1 / B = K IC / H v (μm 0.5 )[Equation 1]
[0129] In equation 1, “B” is the brittleness, “K IC ” is the fracture toughness, and “H v " is the hardness. The unit of the first brittleness index of equation 1 can be "μm 0.5 ”, “B”, “K IC ” and “H v " can be substituted into "μm" as the unit of the first brittleness index 0.5 " converted value.
[0130] In the glass article 100, an index related to brittleness or elastic energy may be defined, which is related to resistance to lower bending fracture in the event of external impact. As brittleness decreases, fracture toughness increases, and hardness decreases, the first brittleness index may have a higher value. As the first brittleness index increases, the glass article 100 may have higher elastic energy and may have excellent resistance to lower bending fracture. In an embodiment, the first brittleness index of the glass article 100 defined by Equation 1 may be 1.5×10 -4 μm 0.5 or larger.
[0131] In an embodiment, other factors related to the first brittleness index of the glass article 100 having a relatively high consistency with the pen drop test result may be further defined. The second brittleness index, the third brittleness index, and the fourth brittleness index of the glass article 100 may be defined by the following Equations 2 to 4 (hereinafter also referred to as Equations 2 (Eq. 2) to 4 (Eq. 4), respectively).
[0132] Second brittleness index = 1 / B×K IC (MPa·m) [Equation 2]
[0133] The third brittleness index = 1 / B × 1 / T g (μm 0.5 / K) [Equation 3]
[0134] Fourth brittleness index = 1 / B × 1 / T g ×E(MPa·μm 0.5 / K)[Equation 4]
[0135] In equations 2 to 4, “B” is brittleness, “K IC ” is the fracture toughness, “T g " is the glass transition temperature, and "E" is the Young's modulus. The unit of the second brittleness index of Equation 2 may be "MPa·m", and the unit of the third brittleness index may be "μm 0.5 / K", and the unit of the fourth brittleness index can be "MPa·μm 0.5 / K". The value converted from the unit of the second brittleness index to the unit of the fourth brittleness index can be substituted into "B", "K IC ”, “T g ” and “E”. The second brittleness index, the third brittleness index, and the fourth brittleness index of Equations 2 to 4 may be defined as indices further including correlations with the fracture toughness, the glass transition temperature, and the Young's modulus in the first brittleness index.
[0136] The free volume index of the glass article 100 may be defined as a factor related to molecular vibration and molecular structure of the glass article 100 under external impact. The free volume index, which is a factor related to the molecular structure of the glass article 100, may vary with the glass transition temperature (T g ) increases and has a lower value. When the glass article 100 has a large amount of space between molecules due to its molecular structure (i.e., when the free volume is large), the molecular structure change may not be affected by external impact, and the crack resistance against external impact may be excellent. However, this may have a trade-off relationship with the bonding strength and the degree of densification of the glass in the glass article 100. In an embodiment, the glass article 100 may have a glass transition temperature (T g), and the brittleness index can satisfy the predetermined numerical range.
[0137] Each of the second to fourth brittleness indexes may further include a factor that takes into account consistency with a pen drop test of the glass article 100. In an embodiment, in the glass article 100, the second brittleness index defined by Equation 2 may be approximately 2.3×10 -10 MPa·m or greater, the third brittleness index defined by Equation 3 may be approximately 2.0×10 -7 μm 0.5 / K or greater, and the fourth brittleness index defined by Equation 4 may be approximately 1.6×10 -2 MPa·μm 0.5 / K or greater.
[0138] Equations 1 to 4 described above may be indexes related to the brittleness of the glass article 100. However, in the present disclosure, the "brittleness index" of the glass article 100 may be an index defined by the equation described above, and may not be completely equivalent to the equations of "brittleness", "fracture toughness", and "glass transition temperature" commonly used in the technical field of the present disclosure. In consideration of consistency with a pen drop test, which is one of the various indicators of the impact resistance of the glass article 100, the "brittleness index" defined in the equation described above may be defined as a partially corrected equation.
[0139] The glass article 100 in the embodiment may have a thickness of 100 μm or less (eg, 20 μm to 100 μm or about 30 μm), and the brittleness indexes of Equations 1 to 4 may satisfy the values within the range described above.
[0140] The glass article 100 is thin and foldable, and thus a relatively high level of impact resistance is desired. As described above, each of the plurality of measurable physical properties of the glass article 100 may not be highly consistent with the pen drop test result and the impact resistance of the glass article 100. In other words, even when the predetermined physical property of the glass article 100 has a relatively high value, the glass article 100 may not necessarily have excellent impact resistance. However, in an embodiment, the factors including the measurable physical properties of the glass article 100 defined by Equations 1 to 4 may have a relatively high consistency with the pen drop test result. Therefore, the degree of the impact resistance of the glass article 100 may be measured by the quantitative factors of the glass article 100.
[0141] In addition, the glass article 100 in the embodiment may have characteristics suitable for a cover window of a foldable display device 500. The glass article 100 may have the impact resistance characteristics and a thin thickness described above, and may satisfy the transparency, the content of foreign matter or cracks per unit area, and the light transmittance sufficient for application to the display device 500. The glass article 100 may have impact resistance characteristics because the brittleness index described above satisfies a predetermined value, and may have physical properties or characteristics desired for a cover window of the display device 500 to provide a clear image to the user.
[0142] In an embodiment, the glass article 100 can have a tensile index (β) in the range of about 0.95 to about 1.00. KWW ). The glass article 100 may be suitable for a cover window of a foldable display device because it has excellent impact resistance while satisfying the brittleness index described above and having a relatively high tensile index. The "tensile index", which is a physical property related to the strength coefficient, the Vogel temperature, and the glass transition temperature, may indicate the mobility and activity of atoms in the glass structure and may verify the structural fluidity of the glass network structure. Since the glass article 100 has a relatively high tensile index, it may have excellent structural fluidity and flexible product characteristics.
[0143] In addition, as described above, the glass article 100 may include SiO 2 、Al 2 O 3 and except Al 2 O 3 Various metal oxides other than 2 O. Li 2 O, CaO or MgO and ZrO 2 ). The physical properties of the glass article 100 may be determined based on the amount of Al contained in the glass article 100. 2 O 3 The content of metal oxides other than Al 2 O 3 In the embodiment, in the glass article 100, in addition to Al 2 O 3 Metal oxides other than 1 2 O, where "R 1 ” is a monovalent metal element) and the content of divalent metal oxides (R 2 O, where "R 2 ” is the content ratio of divalent metal elements) (R 1 2 O / R 2The flux of AlO can be in the range of 5 to 10 and is defined as 2 O 3 The content of 2 O 3 Total content of metal oxides other than 1 2 O+R 2 O) ratio (Al 2 O 3 / (R 1 2 O+R 2 The R-Ratio of (O)) can be in the range of 0.2 to 0.6. In the above formula, "R 1 ” and “R 2 ” are monovalent and divalent metal elements, respectively, and may include “R 1 2 O" and "R 2 An example of O" may be Na 2 O. Li 2 O.K 2 O, CaO or MgO, etc. The glass article 100 has the above-described brittleness index having a predetermined value, a relatively high tensile index, and flux and R-ratio having values within the above-described ranges, and thus may have excellent impact resistance and flexibility.
[0144] Hereinafter, the results of the pen drop test performed on various glass articles 100 and the consistency evaluation between the factors described above will be described.
[0145] Example
[0146] <Preparation Example 1: Preparation of Glass Product>
[0147] A plurality of glass substrates having various compositions were prepared and divided into Sample #1 to Sample #21, and then a glass article preparation process was performed for each sample by the method described above. The glass article for each sample was prepared to have a thickness of 50 μm.
[0148] A sample of the glass article was prepared by the following process.
[0149] The glass article was formed into a glass block by weighing 500 g for each sample using a PtRh10% crucible, increasing the temperature from 1500°C to 1650°C at a rate of 10 K / min, maintaining the temperature for 3 to 6 hours, and rapidly cooling it in a carbon mold at 600°C.
[0150] In order to remove residual stress of the prepared glass block, annealing was performed at a temperature 30° C. higher than the glass transition temperature examined for each sample for 1 to 6 hours, and then the glass block was cooled to 400° C. at a rate of 1 K / min, and then cooled to room temperature, thereby obtaining a glass block having a thickness of 10 mm.
[0151] In order to perform a pencil drop test on the prepared glass block, the glass block was cut into a thickness of 270 μm using a diamond wire saw apparatus, and then polished on opposite sides until the thickness became 50 μm.
[0152] Using KNO 3 Molten salt was processed into 50 μm specimens for chemical strengthening for each sample. The surface compressive stress ("CS") was controlled to be in the range of 700-800 MPa, and the depth of layer ("DoL") was controlled to be in the range of 15%-20% compared to the glass thickness.
[0153] In order to compare the factors defined by the above equations with the actual pen drop test results of the glass product 100, the structural fluidity of the glass product sample was checked by theoretical viscosity calculation, and the impact resistance main factor was checked by physical property analysis. First, the viscosity of the glass was checked by the Vogel-Fulcher-Tahman (VFT) equation, and the following equation (1') (hereinafter also referred to as equation (1') (Eq. (1'))) involves the viscosity and temperature of the glass.
[0154]
[0155] Where η is the viscosity, A VFT is the relatively high temperature limiting viscosity, T is the viscosity measurement temperature, T 0 is the Vogel temperature, and B VFT It is in T 0 The viscosity below.
[0156] In order to examine the fluidity of the glass structure based on the Vogel temperature, the following equation (2') (hereinafter also referred to as equation (2') Eq. (2')) is derived based on the Kohlrausch-Williams-Watt (KWW) formula.
[0157]
[0158] Here, “β KWW " is the tensile index, "D" is the strength coefficient (D = B VFT / T 0 ), "T 0 ” is the Vogel temperature, and “T g ” is the glass transition temperature. Vogel temperature (T 0) indicates the ideal glass transition temperature (T g ), and generally refers to the point at which the free volume expected for the relaxation of the glass network structure is theoretically zero and is not affected by manufacturing conditions such as cooling rate, volume, and defects of the glass sample. Therefore, the viscosity when the glass network structure is formed can be compared by Vogel temperature comparison. In addition, the Vogel temperature (T 0 ) calculated stretch index (β KWW ) can indicate the mobility and activity of atoms in the glass structure and can verify the structural fluidity of the glass network structure.
[0159] Next, the physical properties of the glass article for each sample were measured and compared to the Vogel temperature (T 0 ) and the stretch index (β KWW ) are shown in Table 1 below. The measured physical properties of the glass articles include the coefficient of thermal expansion (CTE), the glass transition temperature (T g ), density (ρ), Young's modulus (E), Poisson's ratio (v), hardness (H v ), fracture toughness (K IC ) and brittleness (B).
[0160] Here, the glass transition temperature (T) was examined by preparing 5 g of each glass sample using a differential thermal analysis ("DTA") apparatus and increasing the temperature to the glass transition temperature range at a rate of 10 K / min. g ). The thermal expansion coefficient of the glass was examined by preparing a specimen having a size of 10 mm×10 mm×13 mm for each composition using a thermomechanical analyzer (“TMA”) apparatus and increasing the temperature to the glass transition temperature range at a rate of 10 K / min.
[0161] The Poisson's ratio was examined by manufacturing a test specimen having a size of 10 mm×20 mm×3 mm for each composition and examining stress and strain of the test specimen using an elastic modulus tester apparatus.
[0162] The hardness (H) was calculated by applying a load of 4.9 Newtons (N) for 30 seconds using a diamond tip having a size of 19 μm with a Vickers hardness tester apparatus, by the following equation (3′) and equation (4′) (hereinafter also referred to as equation (3′) (Eq. (3′)) and equation (4′) (Eq. (4′)) respectively). v ) and fracture toughness (K IC ).
[0163]
[0164] Among them, "H v” indicates Vickers hardness, “F” indicates load, and “a” indicates indentation length.
[0165]
[0166] Among them, "K IC ” indicates fracture toughness, “φ” indicates constraint index (φ≈3), and “H v ” indicates Vickers hardness, “K” indicates a constant (K=3.2), “c” indicates a crack length, and “a” indicates an indentation length.
[0167] The brittleness (B) was calculated by the following equation (5') (hereinafter also referred to as equation (5') (Eq. (5')) by applying a load of 4.9 N for 30 seconds using a Vickers hardness tester apparatus.
[0168]
[0169] Where, "B" is brittleness and "γ" is a constant (γ = 2.39N 1 / 4 / μm 1 / 2 ), “P” is the indentation load, “a” is the indentation length, and “C” is the crack length.
[0170] The crack initiation load was measured using a Vickers hardness tester device.
[0171] [Table 1]
[0172]
[0173] In Table 1, “CTE” is the coefficient of thermal expansion, “T g ” is the glass transition temperature, “ρ” is the density, “E” is the Young’s modulus, “v” is the Poisson’s ratio, and “H v ” is the hardness, and “K IC ” is fracture toughness, and “B” is brittleness.
[0174] <Test Example 1: Impact Resistance Evaluation - Pen Drop (Ball Diameter 0.7 mm) Test>
[0175] like Fig. 9 As shown in , a pen drop test ("PDT") was performed using the glass article sample prepared in Preparation Example 1.
[0176] Fig. 9 : is a figure which shows an example of the PDT method of a glass product.
[0177] refer to Fig. 9, a glass product sample GP having a thickness of 50 μm is prepared, and it is bonded to a polyethylene film substrate SUB having a thickness of 250 μm and modularized. In an embodiment, the glass product sample GP and the polyethylene film substrate SUB may be disposed on a base substrate STA. After the glass product sample GP and the polyethylene film substrate SUB are bonded and cured for more than 30 minutes, PDT is performed. PDT is performed by dropping a pen PEN having a ball diameter of 0.7 mm and a weight of 1.12 g at a temperature of 20° C. to 22° C. and a humidity of 30% using an automatic dropping device ADB until a break occurs in the glass product sample GP. The drop height H is increased at intervals of 0.5 cm using a drop height control device HCS, and the glass product sample GP is observed by a microscope after one impact to check whether cracks or breakages have occurred. The drop height H is defined as the vertical distance from the glass product sample GP to the drop height control device HCS.
[0178] PDT was performed 30 times on three or more identical glass product samples GP, and an average value was measured and shown in the following Table 2. In addition, the physical properties measured in Preparation Example 1, the brittleness index calculated by Equation 1 to Equation 4, and the tensile index were calculated and shown in the following Table 2. The crack occurrence height shown in Table 2 refers to the drop height H measured when the glass product sample GP has a crack.
[0179] [Table 2]
[0180]
[0181]
[0182] In Table 2, the glass article samples GP are arranged in order of excellent to poor pen drop test ("PDT") results. In PDT, sample #1 has excellent impact resistance because cracks are generated at the highest position, and sample #21 has poor impact resistance because cracks are generated at the lowest position.
[0183] Referring to Table 2, it is clear that the PDT results and the values of Equations 1 to 4 show substantially the same trend. It is clear that the samples having relatively small brittleness indexes of Equations 1 to 4 substantially have poor PDT results. In particular, it is clear that the fourth brittleness index defined by Equation 4 shows the highest consistency with the result value of PDT. When the brittleness index described above is small, it can be predicted that the impact resistance is poor. On the contrary, it is clear that the samples having relatively large brittleness indexes of Equations 1 to 4 show excellent PDT results. That is, when the brittleness index described above is large, it can be predicted that the impact resistance is excellent.
[0184] In addition, it is clear that among the samples, sample #1 and sample #2 have a crack occurrence height of 6 cm or more, and have a tensile index of 0.95 or more or 0.990 or more. It is clear that sample #1 and sample #2 have excellent impact resistance according to the PDT results, and have excellent flexibility according to the relatively high tensile index. As in the case of sample #1 and sample #2, the glass article 100 in the example (see Figure 1 ) may have excellent physical properties sufficient to be applied to a cover window of a foldable display device.
[0185] In summarizing the detailed description, it will be appreciated by those skilled in the art that many changes and modifications may be made to the preferred embodiments without departing substantially from the principles of the present disclosure. Therefore, the preferred embodiments of the present invention disclosed are used in a general and descriptive sense only and not for the purpose of limitation.
Claims
1. A glass product, wherein: The glass product comprises: a first surface; and a second surface, facing away from the first surface in the thickness direction, wherein the thickness from the first surface to the second surface is in the range of 20 μm to 100 μm, The first brittleness index defined by the following equation 1 is 1.5×10 -4 μm 0.5 or larger: The first brittleness index = 1 / B = K IC / H v μm 0.5 Equation 1 Among them, "B" is brittleness, "K IC ” is the fracture toughness, and "H v ” is the hardness, and The tensile index defined by the following equation 2' is 0.95 or greater: Where "D" is the strength coefficient, the strength coefficient is B VFT Divide by T0, "T0" is the Vogel temperature, "B VFT ” is the viscosity at T0, and “T g ” is the glass transition temperature.
2. The glass product according to claim 1, wherein: The second fragility index defined by the following equation 2 is 2.3×10 -10 MPa·m or greater: The second brittleness index = 1 / B×K IC MPa·mEquation 2 Where "B" is the brittleness, and "K IC ” is the fracture toughness.
3. The glass product according to claim 1, wherein: The third fragility index defined by the following equation 3 is 2.0×10 -7 μm 0.5 / K: The third brittleness index = 1 / B × 1 / T g μm 0.5 / K Equation 3 Where "B" is the brittleness, and "T g ” is the glass transition temperature.
4. The glass product according to claim 1, wherein: The fourth fragility index defined by the following equation 4 is 1.6×10 -2 MPa·μm 0.5 / K or greater: The fourth brittleness index = 1 / B × 1 / T g ×E MPa·μm 0.5 / K Equation 4 Wherein, "B" is the brittleness, "T g ” is the glass transition temperature, and “E” is Young’s modulus.
5. The glass product according to claim 1, wherein: In a pen drop test performed with a pen having a ball diameter of 0.7 mm and a weight of 1.12 g, a crack occurrence height was 6 cm or more.
6. The glass product according to claim 1, wherein: The glass article is flexible.
7. The glass product according to claim 1, wherein: The glass transition temperature is equal to or lower than 600°C.
8. The glass product according to claim 1, wherein: The glass product comprises SiO2, Al2O3 and metal oxides other than Al2O3, The flux, defined as the ratio of the content of monovalent metal oxide to the content of divalent metal oxide in the metal oxide, is in the range of 5 to 10, and The ratio of the content of Al2O3 to the total content of the metal oxides is in the range of 0.2 to 0.
6.
9. A glass product for a cover window of a foldable display device, wherein: The glass product comprises: a first surface; and a second surface, facing away from the first surface in the thickness direction, wherein the thickness from the first surface to the second surface is in the range of 20 μm to 100 μm, The first brittleness index defined by the following equation 1 is 1.5×10 -4 μm 0.5 or larger: The first brittleness index = 1 / B = K IC / H v μm 0.5 Equation 1 Among them, "B" is brittleness, "K IC ” is the fracture toughness, and "H v " is the hardness, In a pen drop test performed with a pen having a ball diameter of 0.7 mm and a weight of 1.12 g, a crack occurrence height is 6 cm or more, and The glass article is flexible.
10. The glass product according to claim 9, wherein: The second fragility index defined by the following equation 2 is 2.3×10 -10 MPa·m or greater: The second brittleness index = 1 / B×K IC MPa·mEquation 2 Where "B" is the brittleness, and "K IC ” is the fracture toughness.
11. The glass product according to claim 9, wherein: The third fragility index defined by the following equation 3 is 2.0×10 -7 μm 0.5 / K: The third brittleness index = 1 / B × 1 / T g μm 0.5 / K Equation 3 Where "B" is the brittleness, and "T g ” is the glass transition temperature.
12. The glass product according to claim 9, wherein: The fourth fragility index defined by the following equation 4 is 1.6×10 -2 MPa·μm 0.5 / K or greater: The fourth brittleness index = 1 / B × 1 / T g ×E MPa×μm 0.5 / K Equation 4 Wherein, "B" is the brittleness, "T g ” is the glass transition temperature, and “E” is the Young’s modulus.
13. The glass product according to claim 9, wherein: The tensile index defined by the following equation 2' is 0.95 or greater: Where "D" is the strength coefficient, the strength coefficient is B VFT Divide by T0, "T0" is the Vogel temperature, "B VFT ” is the viscosity at T0, and “T g ” is the glass transition temperature.
14. The glass product according to claim 9, wherein: The glass transition temperature is equal to or lower than 600°C.
15. The glass article according to claim 9, wherein: The glass product comprises SiO2, Al2O3 and metal oxides other than Al2O3, The flux, defined as the ratio of the content of monovalent metal oxide to the content of divalent metal oxide in the metal oxide, is in the range of 5 to 10, and The ratio of the content of Al2O3 to the total content of the metal oxides is in the range of 0.2 to 0.
6.
16. A display device, wherein: The display device comprises: A display panel including a plurality of pixels; A cover window is arranged above the display panel, and the cover window comprises: Glass products, said glass products: having a thickness in the range of 20 μm to 100 μm; has a first brittleness index defined by the following equation 1, wherein the first brittleness index is 1.5×10 -4 μm 0.5 or larger: The first brittleness index = 1 / B = K IC / H v μm 0.5 Equation 1 Among them, "B" is brittleness, "K IC ” is the fracture toughness, and "H v ” is the hardness; and Having a tensile index defined by the following equation 2', the tensile index being 0.95 or greater: Where "D" is the strength coefficient, the strength coefficient is B VFT Divide by T0, "T0" is the Vogel temperature, "B VFT ” is the viscosity at T0, and “T g ” is the glass transition temperature; and An optically transparent bonding layer is disposed between the display panel and the cover window.
17. The display device according to claim 16, wherein: The second fragility index defined by the following equation 2 is 2.3×10 -10 MPa·m or greater: The second brittleness index = 1 / B×K IC MPa·mEquation 2 Where "B" is the brittleness, and "K IC ” is the fracture toughness, The third fragility index defined by the following equation 3 is 2.0×10 -7 μm 0.5 / K: The third brittleness index = 1 / B × 1 / T g μm 0.5 / K Equation 3 Where "B" is the brittleness, and "T g ” is the glass transition temperature, and The fourth fragility index defined by the following equation 4 is 1.6×10 -2 MPa·μm 0.5 / K or greater: The fourth brittleness index = 1 / B × 1 / T g ×E MPa·μm 0.5 / K Equation 4 Wherein, "B" is the brittleness, "T g ” is the glass transition temperature, and “E” is Young’s modulus.
18. The display device according to claim 16, wherein: The glass product comprises SiO2, Al2O3 and metal oxides other than Al2O3, The flux, defined as the ratio of the content of monovalent metal oxide to the content of divalent metal oxide in the metal oxide, is in the range of 5 to 10, and The ratio of the content of Al2O3 to the total content of the metal oxides is in the range of 0.2 to 0.
6.
19. The display device according to claim 16, wherein: In a pen drop test performed with a pen having a ball diameter of 0.7 mm and a weight of 1.12 g, the crack occurrence height was 6 cm or more.
20. The display device according to claim 16, wherein: The glass transition temperature is equal to or lower than 600°C.